2015
DOI: 10.1021/acs.jpcb.5b03167
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Analysis of the Impact of Steric Interaction on the Function of Switchable Polarity Solvents

Abstract: A density functional theory (DFT) analysis has been performed to explore the impact of steric interactions on the function of switchable polarity solvents (SPS) and their implications on a quantitative structure-activity relationship (QSAR) model previously proposed for SPS. An X-ray crystal structure of the N,N-dimethylcyclohexylammonium bicarbonate (Hdmcha) salt has been solved as an asymmetric unit containing two cation/anion pairs, with a hydrogen bonding interaction observed between the bicarbonate anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The QSAR model indicated including ring systems which are near or included the nitrogen such as cyclohexyl groups, pyrrolidines, and piperidines facilitates reaching high concentrations in the polar form [20]. Density functional theory (DFT) studies demonstrated that the ring system constrains the organic groups preventing steric disruption at the amine proton [21]. In response we investigated 1-cyclohexylpiperidine (CHP), featuring two ring systems around the nitrogen center.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…The QSAR model indicated including ring systems which are near or included the nitrogen such as cyclohexyl groups, pyrrolidines, and piperidines facilitates reaching high concentrations in the polar form [20]. Density functional theory (DFT) studies demonstrated that the ring system constrains the organic groups preventing steric disruption at the amine proton [21]. In response we investigated 1-cyclohexylpiperidine (CHP), featuring two ring systems around the nitrogen center.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Our initial demonstration of the SPS FO process used dimethylcyclohexylamine (DMCA) [4]. While DMCA is a potential SPS draw solute an SPS optimized for SPS FO process has been sought [15][16][17][18] and suggest 1-cyclohexylpiperidine is an especially promising candidate. Regardless of the SPS employed in the process DMCA is an excellent model SPS and was used to develop the process energy model.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 capture and utilization cycle 1-Cyclohexylpiperidine (CHP) was tested as SPS for the capture and electrochemical reduction of CO 2 based on high CO 2 absorption capacities, up to 189.63 g/L, compatibility with polymeric systems, and expected low production cost. [29][30][31] As capture-electrolyte media for the utilization of CO 2 , CHP presents additional ideal characteristics, such as low volatility, effective polar-to-nonolar phase transition, low membrane permeability, and compatibility with a wide range of materials. 27 A buffer-layer-type cell with a cation exchange (CEM), inspired in the work of Delacourt et al, 23 was used to perform the electrochemical release and reduction of captured CO 2 .…”
Section: Technical Approachmentioning
confidence: 99%